Microscopic polyarteritis: clinical features and treatment. Issue 766 (August 1989) - Rodgers, H.; Guthrie, J. A.; Brownjohn, A. M.; Turney, J. H.
Abstract : The clinical features, treatment and survival of 36 patients with microscopic polyarteritis diagnosed between 1957-1988 have been reviewed. All had a focal segmental necrotizing glomerulonephritis on renal biopsy with evidence of a small vessel vasculitis. Most had a prodromal illness of less than 1 month. Severity of renal disease varied from microscopic haematuria which has a good prognosis to acute oliguric renal failure which carries a high mortality. The prognosis of microscopic polyarteritis can be improved if the condition is recognized early and treated with steroids and cyclophosphamide.